Role of IL6 -174 G/C, IL10 1082G/A and IL10 -592C/A in the pathogenesis of keratoconus and development of recurrent erosion in Ukrainian patients with lattice corneal dystrophy (Ukrainian Journal of Ophthalmology, 2025)
Background: Keratoconus (KC, or corneal ectasia) is a multifactorial disease with a genetic component and an average annual incidence rate of 2.0/100,000 persons. Lattice corneal stromal dystrophy (LCD), a monogenic disorder with varying phenotypic manifestations, is the most common hereditary corneal dystrophy associated with mutations in the TGFBI gene in Ukraine, with as much as 40.2% of cases attributed to this disease.Purpose: To elucidate the role of polymorphic variants in the IL6 promoter (-174 G/C) and IL10 (-1082G/A and -592C/A) as factors of a genetic predisposition to KC and recurrent corneal erosion in Ukrainian patients with LCD.Material and Methods: All patients underwent a routine eye examination including visual acuity assessment, biomicroscopy, fluorescein testing, tonometry and ophthalmoscopy. In addition, patients with KC underwent keratotopography, pachymetry, remote biometry and gonioscopy. Genotyping was done for IL6 -174 G/C, IL10 -1082G/A and IL10 -592C/A by polymerase chain reaction followed by restriction fragment length polymorphism. Fexact test was used for statistical analyses.Results: The frequency of homozygotes (AA) for IL10 rs1800896 was increased, whereas the frequency of homozygotes (CC) for IL6 174G/С was decreased in patients with KC compared to controls (0.25 vs 0.19 and 0.18 vs 0.22, respectively), although the differences were not statistically significant. The frequency of IL6 C allele carriers was significantly higher among patients with LCD and recurrent corneal erosion than controls (0.78 vs 0.66, respectively; p < 0.05). There was a statistically significant difference in the proportion of carriers of the IL10 -592A allele between patients with recurrent corneal erosion and population sample (0.483 vs 0.327, respectively, p < 0.05).Conclusion: IL6 174G/С, IL10 -592С/A and IL10 -1082G/C and the genes determining the pathological processes in the cornea produce a cumulative effect towards modifying the clinical phenotype in keratoconus and lattice corneal dystrophy.
Keywords: keratoconus; lattice corneal dystrophy; recurrent erosions; clinical phenotype; interleukin gene polymorphism; genetic predisposition